An attempt to revisit the global biogeography of limno-terrestrial Tardigrada - Philip J.A. PUGH; Sandra J. McINNES (Journal of Limnology, 2007)
The major increase in distribution records of limno-terrestrial tardigrades over the last ten years has enabled us to reassess the global biogeography of the Tardigrada using cluster analysis, principal components analysis and parsimony analysis of endemism (PAE). Although the new clustergram topology shows a close correlation with those we originally presented in 1998, the PAE outputs warrant a radical reinterpretation of the results as they imply that the Laurasian fauna is derived and the Gondwanan groups basal. The distribution of endemic tardigrade genera and families provides some support for this argument though the findings should be viewed with some caution as PAE has its detractors and has not been previously applied on a 'global' scale.